Pengaruh store atmosphere dan kualitas layanan terhadap minat pembelian ulang melalui kepuasan konsumen sebagai variabel mediasi pada outlet beli kopi di sidoarjo - Manzilah Ar Rohmah; Afifatus Sholikhah (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study aims to determine the effect of store atmosphere and service quality on repurchase intention through consumer satisfaction as a mediating variable at Beli Kopi outlets in Sidoarjo. This study used a quantitative approach with descriptive methods. The population in this study were all Beli Kopi consumers in Sidoarjo, while the research sample consisted of 160 respondents obtained using a non-probability sampling technique with an accidental sampling method. Data collection was conducted by distributing questionnaires using a Likert scale. Data analysis used Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with the assistance of the SmartPLS 4.0 application. The results showed that store atmosphere has a positive and significant effect on consumer satisfaction and repurchase intention. Service quality also has a positive and significant effect on customer satisfaction and repurchase intention. Furthermore, customer satisfaction has a positive and significant effect on repurchase intention. The study also demonstrated that customer satisfaction mediates the influence of store atmosphere and service quality on repurchase intention at Beli Kopi outlets in Sidoarjo. Therefore, the better the store atmosphere and the better the service quality, the higher the level of customer satisfaction, which in turn encourages repeat purchases.